Javanese religion, Islam or syncretism: comparing Woodward’s Islam in Java and Beatty’s Varieties of Javanese Religion - Agus Salim (Indonesian Journal of Islam and Muslim Societies, 2013)
It has been proven that the different findings in examining Javanese religious lifeare led by the differences in terms of academic approaches. It includes the wayssome key terms are perceived and elaborated. The term ‘Islam’ is defined in itswide sense by one and its narrow sense by the other. The popular rite of Slametanis also elaborated its different aspects by different authors, one leading to Islamand the other leading to animism. The notion of mysticism and mystical practicesare also employed to refer to something different, one referring to Sufi tradition,and the other referring to authentic Javanese mystical practices.In addition, authors’ perspectives matter. Particular understanding of some no-tions applied from the beginning of the observation has been guided the attentionto particular aspects of religious life. Certain understanding about Islam has madeone author emphasize more on the aspects of Islam, rather than different reli-gious tradition. On the other hand, an empty-assumption-like autor to conductobservation on religious life of Javanese has been easily fallen to the dominantview of previous examination on the field. Those factors may lead to using differ-ent sort of data. If a single religious tradition like Islam is considered, the useful resources are textual, since they tell much about the general development of thetradition. However, while no single religious tradition is considered more impor-tant than others, one may find that ethnographical account is the best way to seewhat kind of religious traditions exist and how the traditions are perceived andpracticed. Lastly, as the leading notion and the subsequent sort of data used aredifferent, the aspects of a religious tradition are emphasized differently, one thegreat and the other the little tradition. Therefore, the awareness -that ‘there issubjective involvement in the process of knowing’ is confirmed in this thesis. Ithas been proven by the fact that different findings of the same field research arecaused by the ways researchers approach the problem. In fact, they have differ-ent approaches.Telah terbukti bahwa perbedaan temuan dilapangan dalam penelitian tentangkeberagamaan masyarakat Jawa dipicu adanya perbedaan pendekatan penelitian.Perbedaan tersebut diantaranya adalah perbedaan cara memaknai beberapakata kunci. Kata ‘Islam’ oleh satu peneliti didefinisikan secara luas, sementaraoleh peneliti yang lain didefinisikan secara sempit. Pembahasan tentang Slametanjuga ditekankan pada aspek-aspek yang berbeda oleh masing-masing penulis.Hasilnya, sementara yang satu menunjukkan bahwa upacara tersebut Islamik,yang lainnya cenderung animistik. Wacana tentang paham dan praktek mistikjuga dikembangkan mengarah pada klaim yang berbeda, yang satu tradisi Sufi,yang lainnya paham kebatinan asli Jawa.Selanjutnya,  beberapa  point  penting  terkait  dengan  perspektif  yangdikembangakan oleh peneliti. Istilah kunci yang dipegang sejak awal menuntun sipeneliti untuk menekankan pada beberapa aspek kehidupan keberagamaan. Is-lam yang menjadi faktor penentu mengarahkan si peneliti untuk lebih banyakmenekankan data dan penafsirannya pada Islam, daripada tradisi keagamaanlain. Disisi lain, karya yang nampak diawalnya tanpa pretensi apapun tentangtradisi keagamaan tertentu, bahkan mudah jatuh pada tuntunan karya-karyasebelumnya. Faktor-faktor tersebut mengarahkan para peneliti untuk memakaiperangkat data yang berbeda. Jika yang banyak diperhitungkan sejak awal adalahsuatu tradisi keagamaan tertentu, misalkan Islam, sumber yang lebih bergunaadalah text, untuk melihat perkembangan umum dalam beberapa tingkat tradisi.Namun jika tidak ada prioritas satu tradisi tertentu, si peneliti menganggap bahwacatatan ethnography akan lebih banyak berguna. Taerakhir, adanya perbedaan-perbedaan yang telah disebutkan tadi akan mengarahkan pada penekanan padaaspek-aspek tradisi yang berbeda.Dengan demikian, keyakinan bahwa ‘ada pengaruh subjective dalam prosesmengetahui’ sebagaimana yang dikembangkan oleh sosiologi pengetahuan telahterbukti dalam. Faktanya adalah pernbedaan temuan lapangan dipengaruhi olehsecara apa masalah penelitian tersebut didekati. Nyatanya, perangkat penelitianyang mereka gunakan memang berbeda.